THE DEVELOPMENT OF PTC CREO PARAMETRIC WEBSITE MODULE FOR BASIC PARAMETRIC MODELLING WORK - Suheri, Viraldy Abizar; Suherman, Amay; Komaro, Mumu (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2023)
The development of the PTC Creo Parametic website-based learning module for basic modeling work aims to facilitate DPTM UPI students in developing basic parametric modeling skills. The method used is Research Development (RD) with a qualitative approach. In order for the development flow to be directed, the process of developing this learning module uses the Hannafin and Peck development model. The research instrument for module testing used questionnaires, interviews, and observations to find out how the DPTM UPI students responded. This research produced a website-based PTC Creo Parametric learning module for basic parametric modeling work that can facilitate DPTM UPI students and get positive responses from DPTM UPI students. In addition, learning modules provide benefits for users because they are supported by a website-based multitopic scheme, so users can easily access learning materials.